Dampak Self-Management terhadap Mindset Entrepreneurial: Studi Kasus pada UMKM di Kota Pangkalpinang - Ramadona, Dista; Raferdy, Lionnardo Savira; Ammalia, Adinda Risky; Aryansyah, Ary Fakturrachman (Universitas Batanghari, 2024)
This study aims to analyze the impact of self-management on entrepreneurial mindset among Micro, Small, and Medium Enterprise (MSME) owners in Pangkalpinang City. This research uses a quantitative approach with a data collection method through a questionnaire involving 100 respondents of MSME owners in Pangkalpinang City. The data obtained were analyzed using Statistical Package for the Social Sciences (SPSS) software to test the validity, reliability, and relationship between self-management variables and entrepreneurial mindset. The results of the analysis show that there is a significant positive impact between self-management and entrepreneurial mindset, with a coefficient of determination of 0,947. This indicates that improving self-management skills significantly contributes to the development of a proactive, innovative, and adaptive mindset among MSME owners. This research is expected to provide deeper insights and policy recommendations for the development of training and support programs that focus on improving self-management skills and strengthening entrepreneurial mindset, in order to improve the performance and competitiveness of MSMEs in Pangkalpinang City.